High-efficiency antibacterial polyester fabric and preparation method thereof
Patent Information
- Application Number
- CN202311771100.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-21
AI Technical Summary
但同样的聚酯纤维抗菌性较差,而目前常用的纳米银改性,可使聚酯纤维的抗菌性得到明显提升,但是纳米银在聚酯中分散性较差,且容易析出,抗菌性能难以长久维持,限制了其使用领域;不仅如此,聚酯纤维的吸湿性和抗静电性也需进行改善,以满足抗菌面料领域的更高需求
[0031]本发明的面料由改性聚酯纤维、羊毛纤维和维纶纤维混纺制得,羊毛纤维赋予面料舒适性和保暖性;维纶纤维能显著提升面料的吸湿排汗性能;改性聚酯纤维由PET切片与改性碳纳米管熔融共混制得;其中改性碳纳米管能大幅提升面料的抗静电性能,并且通过接枝有机分子链,不仅改善碳纳米管与聚酯纤维的相容性,还能防止有机分子的迁移和渗出,提升了性能的持久性;此外,有机分子链中的各类功能基团能显著提升面料的抗菌性和一定程度的吸湿性与抗静电性能。因此制得的涤纶面料具有稳定高效的抗菌性、吸湿性和抗静电性能,且保暖舒适,在抗菌面料领域具备重要的应用价值。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of antibacterial fiber fabric technology, specifically, it relates to a high-efficiency antibacterial polyester fabric and its preparation method. Background Technology
[0002] Germs exist in all aspects of human life, such as mites, Escherichia coli, Candida albicans, and Staphylococcus aureus. Textiles inevitably become contaminated with pathogens during use. Because ordinary fabrics lack antibacterial properties, the environment in which they are used, including humidity, temperature, and various stains such as sweat and oils, provides a breeding ground for various germs. Especially with the increasing use of textiles in public places, the harm to human health caused by the proliferation and cross-infection of pathogens is immeasurable.
[0003] With the increasing demands for quality of life in modern society, consumers have shifted their focus from the practicality of fabrics to functionality, health, and safety. Therefore, the research and development of antibacterial fibers and fabrics is receiving more and more attention. However, natural fibers generally have poor antibacterial properties, so synthetic fibers are often modified to meet the antibacterial requirements of fabrics.
[0004] Polyester fiber, commonly known as polyester, is the simplest and cheapest of the three major synthetic fibers in terms of processing. It boasts advantages such as high strength, abrasion resistance, good elasticity, resistance to deformation, corrosion resistance, light resistance, good chemical resistance, and easy washing and quick drying. It has a wide range of applications in both civilian textiles (such as clothing, bedding, and decorative fabrics) and industrial fibers (such as filter materials, insulation materials, and tire cords). However, polyester fiber also has relatively poor antibacterial properties. While nano-silver modification can significantly improve the antibacterial properties of polyester fiber, nano-silver has poor dispersion in polyester and is prone to precipitation, making it difficult to maintain antibacterial performance for a long time, thus limiting its application areas. Furthermore, the moisture absorption and antistatic properties of polyester fiber also need improvement to meet the higher demands of the antibacterial fabric industry. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a highly efficient antibacterial polyester fabric and its preparation method.
[0006] The objective of this invention can be achieved through the following technical solutions:
[0007] A method for preparing a high-efficiency antibacterial polyester fabric includes the following steps:
[0008] A1. Place PET chips in a vacuum drying oven and dry for 12 hours. After taking them out, mix them with modified carbon nanotubes and add them to a twin-screw extruder. Melt blending and spinning are used to obtain nascent fibers, which are then stretched to obtain modified polyester fibers.
[0009] A2. Modified polyester fiber, wool fiber, and vinylon fiber are combined on a drawing frame to form a sliver. The sliver is then drafted and twisted on a roving frame, and finally further drafted and twisted on a spinning frame to produce a blended yarn. High-efficiency antibacterial polyester fabric is then produced using a circular knitting machine.
[0010] Furthermore, in step A1, the mass ratio of PET slices to modified carbon nanotubes is 80:5-15.
[0011] Furthermore, in step A2, the mass ratio of modified polyester fiber, wool fiber, and vinylon fiber is 60:25:15.
[0012] The polyester fiber used is an aromatic polyester fiber, which has higher strength and modulus than ordinary polyester fibers, thus improving the strength of the fabric; wool fiber can give the fabric comfort and warmth; vinylon fiber is the most absorbent of the existing synthetic fibers, which can significantly improve the moisture absorption performance of the fabric.
[0013] Furthermore, the modified carbon nanotubes are prepared through the following steps:
[0014] S1. In a three-necked flask equipped with a stirrer, 5-chloro-2-methyl-4-isothiazolin-3-one (CMI) and N,N-dimethylformamide (DMF) were mixed and the stirrer was turned on. Dibutyltin oxide (catalyst), potassium carbonate and hydroxyethyl ethylenediamine were added sequentially. The temperature was slowly raised to 75°C and the reaction was maintained for 3 hours. After the reaction was completed, deionized water was added, the mixture was stirred evenly, filtered, and recrystallized to obtain intermediate 1. The ratio of CMI, DMF, dibutyltin oxide, potassium carbonate, hydroxyethyl ethylenediamine and deionized water was 14.8g:50mL:0.8g:5.3g:10.4g:50mL.
[0015] In the presence of dibutyltin oxide as a catalyst, 5-chloro-2-methyl-4-isothiazolin-3-one and hydroxyethyl ethylenediamine undergo nucleophilic substitution, and potassium carbonate removes the hydrogen chloride generated in the reaction to give intermediate 1; the specific reaction is shown below:
[0016]
[0017] S2. In a three-necked flask equipped with a stirrer, carboxylated carbon nanotubes and DMF were mixed and magnetically stirred for 30 min. Then, intermediate 1, benzenesulfonic acid (dehydrating agent) and DMAP (4-dimethylaminopyridine, catalyst) were added sequentially. The mixture was sonicated in an 80°C water bath for 2 h, then the water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was filtered, washed 3-4 times with anhydrous ethanol, dried, and ground to obtain intermediate 2. The ratio of carboxylated carbon nanotubes, DMF, intermediate 1, benzenesulfonic acid, and DMAP was 10 g: 80 mL: 21.7 g: 20.6 g: 0.5 g.
[0018] Under the action of benzenesulfonic acid and DMAP, the -COOH on the surface of carboxylated carbon nanotubes undergoes an esterification reaction with the hydroxyl groups on intermediate 1 to obtain intermediate 2; the specific reaction process is shown below:
[0019]
[0020] S3. Under nitrogen protection, intermediate 2 was mixed with DMF in a three-necked flask equipped with a stirrer. After magnetic stirring for 45 min, 3-chloro-1,2-propanediol, potassium carbonate, and dibutyltin dilaurate (catalyst) were added. The mixture was sonicated in an 85°C water bath for 3 h, then the water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was then filtered, washed 3-4 times with anhydrous ethanol, dried, and ground to obtain intermediate 3. The ratio of intermediate 2, DMF, 3-chloro-1,2-propanediol, potassium carbonate, and dibutyltin dilaurate was 10 g: 80 mL: 25.4 g: 6.2 g: 0.3 g.
[0021] Catalyzed by dibutyltin dilaurate, intermediate 2 undergoes nucleophilic substitution with 3-chloro-1,2-propanediol, with excess 3-chloro-1,2-propanediol ensuring that both secondary amino groups on intermediate 2 react. Potassium carbonate removes the hydrogen chloride generated in the reaction, yielding intermediate 3. The specific reaction process is shown below:
[0022]
[0023] S4. In a three-necked flask equipped with a stirrer, intermediate 3 and iodomethane are mixed and stirred evenly, ultrasonically dispersed for 10 min, the reaction temperature is controlled at 80℃, the reaction is carried out for 8 h, the reaction is completed, the mixture is distilled under reduced pressure, washed, cooled and dried to obtain modified carbon nanotubes; the ratio of intermediate 3 to iodomethane is 10 g: 100 mL.
[0024] The tertiary amine on intermediate 3 undergoes an alkylation reaction with excess iodomethane to yield modified carbon nanotubes (quaternized product); the structure of the modified carbon nanotubes is shown in the figure below:
[0025]
[0026] The modified carbon nanotubes obtained are grafted with organic molecular chains through chemical bonding, forming an organic layer on their surface. This significantly improves the interfacial compatibility between carbon nanotubes and polyester fibers, thereby promoting the uniform dispersion of modified carbon nanotubes in polyester fibers. This fully utilizes the antistatic properties of carbon nanotubes and also reinforces the polyester fibers. Furthermore, grafting organic molecular chains onto carbon nanotubes effectively prevents the migration and exudation of organic molecules, ensuring the durability of various properties. The ester groups further enhance the compatibility with polyester fibers. In addition, the organic molecular chains contain multiple hydroxyl groups, isothiazolinones, and quaternary ammonium salt ion structures. The multiple hydroxyl groups not only form chemical bonds with the polyester molecular chains during melt spinning, increasing the interaction force of the polyester fiber matrix and making it less prone to detachment during rinsing, thus improving performance durability, but also enhance the hydrophilicity of the polyester fiber. Furthermore, isothiazolinone possesses excellent properties such as strong antibacterial activity, environmental safety, and a broad antibacterial spectrum. It forms disulfide bonds with the sulfhydryl groups on cysteine residues in bacterial proteins through the active sites of the heterocyclic bonds, thereby inactivating the proteins and achieving bactericidal effects, thus endowing the polyester fiber with significant antibacterial properties. Finally, the introduction of quaternary ammonium salt ions, due to the strong electrostatic interaction between their positive and negative charges on the bacterial cells, results in a strong adsorption effect on the bacteria, which can synergistically enhance the antibacterial properties of the polyester fiber. Moreover, quaternary ammonium salt ions also provide certain antistatic properties.
[0027] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps:
[0028] Carbon nanotubes were placed in an Erlenmeyer flask, then mixed acid was added, and the mixture was ultrasonically treated in a 50°C water bath for 6 hours. After the mixture cooled to room temperature, it was diluted with deionized water, centrifuged, and washed 4-5 times with anhydrous ethanol and deionized water, respectively. The mixture was then dried and ground to obtain carboxylated carbon nanotubes. The mixed acid was a mixture of 98% concentrated sulfuric acid and 37.5% concentrated hydrochloric acid in a volume ratio of 4:1. The ratio of carbon nanotubes to mixed acid was 1 g: 100 mL.
[0029] By subjecting carbon nanotubes to ultrasonic shearing and oxidation with strong acids, a certain number of hydroxyl and carboxyl active groups can be introduced into the sidewalls and tips of the carbon nanotubes, laying the foundation for reaction sites in subsequent chemical reactions.
[0030] The beneficial effects of this invention are:
[0031] The fabric of this invention is made from a blend of modified polyester fiber, wool fiber, and vinylon fiber. Wool fiber imparts comfort and warmth to the fabric; vinylon fiber significantly improves the fabric's moisture-wicking properties; the modified polyester fiber is obtained by melt blending PET chips with modified carbon nanotubes; wherein the modified carbon nanotubes greatly enhance the fabric's antistatic properties, and by grafting organic molecular chains, not only is the compatibility between carbon nanotubes and polyester fibers improved, but the migration and exudation of organic molecules are also prevented, thus enhancing the durability of the properties; in addition, various functional groups in the organic molecular chains significantly enhance the fabric's antibacterial properties and a certain degree of moisture absorption and antistatic properties. Therefore, the resulting polyester fabric has stable and efficient antibacterial, moisture-wicking, and antistatic properties, and is warm and comfortable, possessing significant application value in the field of antibacterial fabrics. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] Example 1
[0034] Preparation of carboxylated carbon nanotubes:
[0035] 20g of carbon nanotubes were placed in an Erlenmeyer flask, and then 2000mL of concentrated sulfuric acid (98% by mass) and concentrated hydrochloric acid (37.5% by mass) were added in a volume ratio of 4:1 to obtain a mixed acid. The mixture was ultrasonically treated in a 50℃ water bath for 6h. After the mixture cooled to room temperature, it was diluted with deionized water, centrifuged, and washed 4 times with anhydrous ethanol and deionized water, dried, and ground to obtain carboxylated carbon nanotubes.
[0036] Example 2
[0037] Preparation of modified carbon nanotubes:
[0038] S1. In a three-necked flask equipped with a stirrer, 14.8 g of CMI and 50 mL of DMF were mixed and the stirrer was turned on. 0.8 g of dibutyltin oxide, 5.3 g of potassium carbonate and 10.4 g of hydroxyethyl ethylenediamine were added in sequence. The temperature was slowly raised to 75 °C and the reaction was maintained for 3 h. After the reaction was completed, 50 mL of deionized water was added, the mixture was stirred evenly, filtered, and recrystallized to obtain intermediate 1.
[0039] S2. In a three-necked flask equipped with a stirrer, 10g of carboxylated carbon nanotubes were mixed with 80mL of DMF. After stirring magnetically for 30min, 21.7g of intermediate 1, 20.6g of benzenesulfonic acid and 0.5g of DMAP were added sequentially. The mixture was sonicated in an 80℃ water bath for 2h, and then the water bath was removed and the mixture was stirred magnetically at room temperature for 6h. The mixture was then filtered, washed three times with anhydrous ethanol, dried, and ground to obtain intermediate 2.
[0040] S3. Under nitrogen protection, 10 g of intermediate 2 was mixed with 80 mL of DMF in a three-necked flask equipped with a stirrer. After stirring magnetically for 45 min, 25.4 g of 3-chloro-1,2-propanediol, 6.2 g of potassium carbonate and 0.3 g of dibutyltin dilaurate were added. The mixture was sonicated in an 85 °C water bath for 3 h, then the water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was then filtered, washed four times with anhydrous ethanol, dried, and ground to obtain intermediate 3.
[0041] S4. In a three-necked flask equipped with a stirrer, 10g of intermediate 3 and 100mL of iodomethane were mixed and stirred evenly, ultrasonically dispersed for 10min, and the reaction temperature was controlled at 80℃. The reaction was carried out for 8h. After the reaction was completed, the mixture was distilled under reduced pressure, washed, cooled and dried to obtain modified carbon nanotubes.
[0042] Example 3
[0043] Preparation of modified carbon nanotubes:
[0044] S1. In a three-necked flask equipped with a stirrer, 29.6 g of CMI and 100 mL of DMF were mixed and the stirrer was turned on. 1.6 g of dibutyltin oxide, 10.6 g of potassium carbonate and 20.8 g of hydroxyethyl ethylenediamine were added in sequence. The temperature was slowly raised to 75 °C and the reaction was maintained at this temperature for 3 h. After the reaction was completed, 50 mL of deionized water was added, the mixture was stirred evenly, filtered, and recrystallized to obtain intermediate 1.
[0045] S2. In a three-necked flask equipped with a stirrer, 20g of carboxylated carbon nanotubes were mixed with 160mL of DMF and magnetically stirred for 30min. Then, 43.4g of intermediate 1, 41.2g of benzenesulfonic acid and 1g of DMAP were added sequentially. The mixture was sonicated in an 80℃ water bath for 2h, and then the water bath was removed and the mixture was magnetically stirred at room temperature for 6h. The mixture was then filtered, washed three times with anhydrous ethanol, dried, and ground to obtain intermediate 2.
[0046] S3. Under nitrogen protection, 20 g of intermediate 2 was mixed with 160 mL of DMF in a three-necked flask equipped with a stirrer. After stirring magnetically for 45 min, 50.8 g of 3-chloro-1,2-propanediol, 12.4 g of potassium carbonate and 0.6 g of dibutyltin dilaurate were added. The mixture was sonicated in an 85 °C water bath for 3 h, then the water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was then filtered, washed four times with anhydrous ethanol, dried, and ground to obtain intermediate 3.
[0047] S4. In a three-necked flask equipped with a stirrer, 20g of intermediate 3 and 200mL of iodomethane were mixed and stirred evenly, ultrasonically dispersed for 10min, and the reaction temperature was controlled at 80℃. The reaction was carried out for 8h. After the reaction was completed, the mixture was distilled under reduced pressure, washed, cooled and dried to obtain modified carbon nanotubes.
[0048] Example 4
[0049] A1. Place 80g of PET chips in a vacuum drying oven and dry for 12 hours. After taking them out, mix them with 5g of modified carbon nanotubes prepared in Example 2, add them to a twin-screw extruder, melt blend and spin to obtain nascent fibers, and then stretch them to obtain modified polyester fibers.
[0050] A2. Combine 60g of modified polyester fiber, 25g of wool fiber, and 15g of vinylon fiber on a drawing frame to form a sliver. Draft and twist the sliver on a roving frame, and then further draft and twist it on a spinning frame to form a blended yarn. Use a circular knitting machine to weft knit the yarn to obtain a high-efficiency antibacterial polyester fabric.
[0051] Example 5
[0052] Unlike Example 4, the modified carbon nanotubes in step A1 were prepared according to Example 3, and the amount used was 10g.
[0053] Example 6
[0054] Unlike Example 4, the modified carbon nanotubes in step A1 were prepared according to Example 3, and the amount used was 15g.
[0055] Comparative Example 1
[0056] Unlike Example 4, ordinary carbon nanotubes are used in step A1.
[0057] Comparative Example 2
[0058] It uses commercially available polyester antibacterial fabric (8% silver fiber, 92% polyester) produced by Advanced Institute (Shenzhen) Technology Co., Ltd.
[0059] The fabrics from Examples 4-6 and Comparative Examples 1-2 were made into corresponding shapes according to different testing standards, and the following performance tests were conducted:
[0060] The inhibition rates of Escherichia coli and Staphylococcus aureus before and after 30 washes were tested according to the national standard GB / T 20944.2-2007 "Evaluation of antimicrobial properties of textiles - Part 2: Absorption method".
[0061] The surface charge density (uC / m³) of the fabric was determined according to the national standard GB / T 12703.2-2009 "Textiles - Electrostatic Test Methods - Part 2: Surface Charge Density". 2This allows for testing of antistatic properties (the lower the surface charge density, the better the antistatic properties).
[0062] The water absorption rate, water droplet diffusion time, and wicking height were determined according to the national standard GB / T 21655.1-2008 "Evaluation of moisture absorption and quick-drying properties of textiles - Part 1: Single combination test method".
[0063] The measurement results are shown in Table 1 and Table 2:
[0064]
[0065] As shown in the table above, in Examples 4-6, with the continuous increase of the amount of modified carbon nanotubes, the antibacterial, moisture-absorbing, and antistatic properties of the fabric all increased. Furthermore, compared with commercially available polyester antibacterial fabrics, the antibacterial properties were stronger and more durable. Therefore, the resulting polyester fabric possesses stable and efficient antibacterial, moisture-absorbing, and antistatic properties, and has significant application value in the field of antibacterial fabrics.
[0066] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0067] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-efficiency antibacterial polyester fabric, characterized in that, Includes the following steps; S1. In a three-necked flask, CMI and DMF are mixed and stirred evenly. Dibutyltin oxide, potassium carbonate and hydroxyethyl ethylenediamine are added in sequence. The temperature is slowly raised to 75°C and the reaction is maintained for 3 hours. Deionized water is added, the mixture is stirred evenly, filtered, and recrystallized to obtain intermediate 1. S2. In a three-necked flask, carboxylated carbon nanotubes were mixed with DMF and magnetically stirred for 30 min. Then, intermediate 1, benzenesulfonic acid and DMAP were added in sequence. The mixture was sonicated in an 80°C water bath for 2 h. The water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was filtered, washed 3-4 times with anhydrous ethanol, dried, and ground to obtain intermediate 2. S3. Under nitrogen protection, intermediate 2 was mixed with DMF in a three-necked flask and magnetically stirred for 45 min. Then, 3-chloro-1,2-propanediol, potassium carbonate and dibutyltin dilaurate were added. The mixture was sonicated in an 85°C water bath for 3 h. The water bath was removed and the mixture was magnetically stirred at room temperature for 6 h. The mixture was then filtered, washed 3-4 times with anhydrous ethanol, dried, and ground to obtain intermediate 3. S4. In a three-necked flask, intermediate 3 and iodomethane were mixed and stirred evenly, ultrasonically dispersed for 10 min, the reaction temperature was controlled at 80℃, the reaction was carried out for 8 h, vacuum distilled, washed, cooled and dried to obtain modified carbon nanotubes. S5. Modified polyester fiber is prepared by melt blending PET chips with modified carbon nanotubes and spinning. The modified polyester fiber is then used to make blended yarn, and high-efficiency antibacterial polyester fabric is obtained by weft knitting on a circular knitting machine.
2. The method for preparing a high-efficiency antibacterial polyester fabric according to claim 1, characterized in that, In step S1, the ratio of CMI, DMF, dibutyltin oxide, potassium carbonate, hydroxyethyl ethylenediamine, and deionized water is 14.8g:50mL:0.8g:5.3g:10.4g:50mL.
3. The method for preparing a high-efficiency antibacterial polyester fabric according to claim 1, characterized in that, In step S2, the ratio of carboxylated carbon nanotubes, DMF, intermediate 1, benzenesulfonic acid, and DMAP is 10g:80mL:21.7g:20.6g:0.5g.
4. The method for preparing a high-efficiency antibacterial polyester fabric according to claim 1, characterized in that, In step S3, the ratio of intermediate 2, DMF, 3-chloro-1,2-propanediol, potassium carbonate, and dibutyltin dilaurate is 10g:80mL:25.4g:6.2g:0.3g.
5. The method for preparing a high-efficiency antibacterial polyester fabric according to claim 1, characterized in that, In step S4, the ratio of intermediate 3 to iodomethane is 10g:100mL.
6. A high-efficiency antibacterial polyester fabric, characterized in that, Prepared according to the method described in any one of claims 1-5.
Citation Information
Patent Citations
Antibacterial polyester fiber and preparation method thereof
CN111074372A
Anti-static warm-keeping fabric
CN116837518A